THEORETICAL BASIS IN STUDYING THE ISSUES THAT PERTAIN TO THE PROFESSIONAL AND COMMUNICATIVE COMPETENCE OF FUTURE TRANSLATORS IN THE AREA OF AVIATION - Білоус, Н. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The paper considers the aspects related to the issues that may arise in reference to the development of professional and communicative competence displayed by future translators in the area of aviation. The studies described in this paper are focused on the influence of the competency-based approach on the training process aimed to achieve highly qualified educational standards regarding the communicative skills and capabilities of specialists in translation in order to efficiently perform the activities in the aviation area. The way to define and solve the issues mentioned above is shown. The results of preceding studies on the professional training of translators are taken into account. The author justifies the organizational and didactic model of the training process and experimentally proves its effectiveness. The paper also discusses the basis for the formation of the professional ethics inherent in translators in the aviation area, which is deemed to be social and humanitarian subjects and special integrative profession- oriented courses. The studies carried out by the author allow one to improve the methods of teaching specialized English, as well as to form the means of communicative competence and professional speaking skills of future specialists in aviation and astronautics, avionics, and air navigation.